Shaping success: clinical implementation of a 3D-printed electron cutout program in external beam radiation therapy - Schulz, Joseph B.; Gibson, Clinton; Dubrowski, Piotr; Marquez, Caroline M.; Million, Lynn; Qian, Yushen; Skinner, Lawrie; Yu, Amy S. (Frontiers in Oncology, 2023)
Purpose The integration of 3D-printing technology into radiation therapy (RT) has allowed for a novel method to develop personalized electron field-shaping blocks with improved accuracy. By obviating the need for handling highly toxic Cerrobend molds, the clinical workflow is significantly streamlined. This study aims to expound upon the clinical workflow of 3D-printed electron cutouts in RT and furnish one year of in-vivo dosimetry data.3D-printed electron cutouts for 6x6 cm, 10x10 cm, and 15x15 cm electron applicators were designed and implemented into the clinical workflow after dosimetric commissioning to ensure congruence with the Cerrobend cutouts. The clinical workflow consisted of four parts: i) the cutout aperture was extracted from the treatment planning system (TPS). A 3D printable cutout was then generated automatically through custom scripts; ii) the cutout was 3D-printed with PLA filament, filled with tungsten ball bearings, and underwent quality assurance (QA) to verify density and dosimetry; iii) in-vivo dosimetry was performed with optically stimulated luminescence dosimeters (OSLDs) for a patient's first treatment and compared to the calculated dose in the TPS; iv) after treatment completion, the 3D-printed cutout was recycled.QA and in-vivo OSLD measurements were conducted (n=40). The electron cutouts produced were 6x6 cm (n=3), 10x10 cm (n=30), and 15x15 cm (n=7). The expected weight of the cutouts differed from the measured weight by 0.4 ± 1.1%. The skin dose measured with the OSLDs was compared to the skin dose in the TPS on the central axis. The difference between the measured and TPS doses was 4.0 ± 5.2%.The successful clinical implementation of 3D-printed cutouts reduced labor, costs, and removed the use of toxic materials in the workplace while meeting clinical dosimetric standards.